Development and Application of a High-Throughput Functional Metagenomic Screen for Glycoside Phosphorylases. Issue 7 (18th July 2019) - Macdonald, Spencer S.; Armstrong, Zachary; Morgan-Lang, Connor; Osowiecka, Magdalena; Robinson, Kyle; Hallam, Steven J.; Withers, Stephen G.
Summary: Glycoside phosphorylases (GPs) catalyze the reversible phosphorolysis of glycosidic bonds, releasing sugar 1-phosphates. To identify a greater range of these under-appreciated enzymes, we have developed a high-throughput functional screening method based on molybdenum blue formation. In a proof-of-principle screen focused on cellulose-degrading GPs we interrogated ∼23, 000 large insert (fosmid) clones sourced from microbial communities inhabiting two separate environments and identified seven novel GPs from carbohydrate active enzyme family GH94 and one from GH149. Characterization identified cellobiose phosphorylases, cellodextrin phosphorylases, laminaribiose phosphorylases, and a β-1, 3-glucan phosphorylase. To demonstrate the versatility of the screening method, varying substrate combinations were used to identify GP activity from families GH13, GH65, GH112, and GH130 in addition to GH94 and GH149. These pilot screen and substrate versatility results provide a screening paradigm platform for recovering diverse GPs from uncultivated microbial communities acting on different substrates with considerable potential to unravel previously unknown degradative pathways within microbiomes. Graphical Abstract: Highlights: Establishment of a high-throughput metagenomic screen for GP activity Identification of seven new GPs from CAZy family GH94 Identification of one new GP from CAZy family GH149 GP activities can be targeted from CAZy families GH13, GH65, GH112, and GH130 Abstract : Macdonald et al. designed a high-throughput screening method to identify a class of enzymes known as glycoside phosphorylases (GPs) from DNA recovered directly from the environment. Their screen yielded 8 new GPs and establishes a platform method for future screening efforts to discover more diverse GPs from environmental DNA.